Vacuum Distillate Catalytic Cracking Technology Modelling: Feedstock and Products Composition and Properties Investigation; Petroleum and Coal; Vol. 62, iss. 2 - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Oreshina А. А. Aleksandra Aleksandrovna; Vymyatnin E. K. Evgeny Konstantinovich; Seytenova G. Gayni; Burumbaeva G. R. Galiya Rashidovna (2020, 2020)
Title screen